Metode Wirbelgruppen dalam Keterampilan Berbicara Bahasa Jerman - Andi Tenri Husni; Abdul Kasim Achmad; Nurming Saleh (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract. This research is classroom action research which consists of two cycles. The purpose of this research to know the planning, process, and results the Wirbelgruppen method in improving the German speaking skills of class X MIPA 5 students of SMA Negeri 1 Barru. This research data consists of quantitative data and qualitative. Qualitative data was obtained through observation and quantitative data was obtained through the results of the German speaking skills test in cycle I and cycle II. The data were analyzed using the percentage technique. The results showed that the percentage value obtained by students in the first cycle reached 58% and the second cycle reached 81%. These results show that the Wirbelgruppen method can improve the German speaking skills of students of class X MIPA 5 SMA Negeri 1 Barru. Keywords: The Wirbelgruppen, Speaking Skills, German